2022
DOI: 10.3897/subtbiol.42.80274
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Chaimowiczia from the karstic Serra do Ramalho plateau, Brazil (Oniscidea, Synocheta, Styloniscidae)

Abstract: Chaimowiczia belongs to the subfamily Iuiuniscinae, family Styloniscidae, and is currently composed of two troglobitic species: C. tatus and C. uai, both occurring in Brazil. A new species of Styloniscidae found in Brazil (Bahia state, Serra do Ramalho, Serra Verde cave) was allocated into this genus by the antenna flagellum with three articles; rectangular-shaped lateral pereonites epimera not apically acute and apex of pleopod 2 endopod with an acute tip and an acute or rounded lobe directed outwards. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, they also found that aquatic species have a shorter shelf life than terrestrial ones and that the shelf life of newly discovered invertebrate species is shorter than for plant or vertebrate species. For recently described isopod species, shelf life varied between 0 years ( Monticelli Cardoso, Bastos-Pereira & Lopes Ferreira, 2022 ) and 54 years ( Williams, Boyko & Marin, 2020 ) with an overall tendency toward the lower range of the spectrum. For example, Malek-Hosseini et al (2022) described a new groundwater species from Iran within three years of sampling, additionally using molecular data to corroborate its species status.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also found that aquatic species have a shorter shelf life than terrestrial ones and that the shelf life of newly discovered invertebrate species is shorter than for plant or vertebrate species. For recently described isopod species, shelf life varied between 0 years ( Monticelli Cardoso, Bastos-Pereira & Lopes Ferreira, 2022 ) and 54 years ( Williams, Boyko & Marin, 2020 ) with an overall tendency toward the lower range of the spectrum. For example, Malek-Hosseini et al (2022) described a new groundwater species from Iran within three years of sampling, additionally using molecular data to corroborate its species status.…”
Section: Discussionmentioning
confidence: 99%
“…However, these conclusions are still under debate. About 480 species of Oniscidea have been recorded in South America, most of them placed in the families Philosciidae Kinahan, 1857 andScleropactidae Verhoeff, 1938 (Schmalfuss 2003;Schmidt & Leistikow 2005;Schmidt 2007;Campos-Filho et al 2018a, 2020, 2021bCardoso et al 2020aCardoso et al , 2020bCardoso et al , 2021Cardoso et al , 2022aCardoso et al , 2022bOcampo-Maceda et al 2022;Carpio-Díaz et al 2018Grangeiro et al 2021;López-Orozco et al 2016. To date, in Peru, 24 species distributed in 12 genera are known so far, i.e., Ligia Fabricius, 1798 (1 sp.)…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, more than 220 species of Oniscidea are known, of which 79 were recorded in caves. Among them, 38 are considered troglobites (obligatory cave-dwellers) and several are troglophiles (facultative cave-dwellers) (Trajano & Carvalho 2017; Campos-Filho et al 2018a, 2019, 2020, 2022a, b, c; Fernandez et al 2019; Cardoso et al 2020a, 2020b, 2021, 2022a, 2022b, 2023; Bastos-Pereira et al 2022). However, for some Oniscidea taxa, these subterranean categories were not properly assigned due to the lack of efficient sampling outside caves.…”
Section: Introductionmentioning
confidence: 99%